(untitled) (Journal Of Educational and Psychological Researches, 2016)
The great scientific evolution and the expansion of the demands of life, especially in the field of architectural design make human’s need increased to use his abilities and all possibilities in active way to have a main role in this progress. To achieve his role in this progression which is can not be achieved and accomplished only by depending on the mental capacity including intelligence spatial / visual, which is one of the branches of the theory of multiple intelligences. This theory is one of the most important theories which we strongly need it to reveal this type of intelligence in order to know the teachers on learners’ abilities to put appropriate methods to deal with them.of this current research as follows: Knowing the degree of spatial intelligence at the University 2. Knowing the differences in spatial intelligence between students according to the following variables "( type, stage) The current research community is determined for students (Faculty of Engineering / Department of Architecture) in Baghdad and Technological University of all academic levels for the academic year (2014-2015).In order to verify the aims of the study, the researchers construct an intelligence spatial taste. The sample is represented by (330) students of University of Baghdad and Technological University.The researchers use the statistical tools to find out the validity and reliability. The results of the study show that: 1-Search Results showed spatial intelligence in level below the average. there is a statistically significant differences depending on the variable stage and in favor of the fourth and fifth phase. The presence of a statistically significant differences between the two groups of students depending on the variable type and in favor of males.